Anaerobic curing composition

JP2024515112A5Pending Publication Date: 2025-04-28HENKEL KGAA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023564675
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-04-21
Filing Date
2022-04-21
Publication Date
2025-04-28

AI Technical Summary

Technical Problem

Existing anaerobic threadlockers face issues such as incomplete curing through large gaps, exposure to air leading to uncured adhesive migration, and poor solvent resistance, which can cause contamination and hazardous conditions.

Method used

A solid anaerobic curable composition comprising a liquid (meth)acrylate monomer, solid thermoplastic polyether polyurethane resin, and a curing component, which can be applied in tape or filament form, providing a dry feel and maintaining integrity at high temperatures, ensuring complete curing and robust adhesion.

Benefits of technology

The composition achieves effective thread locking with high failure torque and adhesion, maintaining integrity at temperatures up to 180°C, preventing adhesive migration and ensuring reliable bonding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2022223737000001
    Figure 2022223737000001
Patent Text Reader

Abstract

An anaerobic curable composition comprising a liquid anaerobic curable component, a solid anaerobic curable component, a solid polyether thermoplastic polyurethane resin, and a curing component for curing said anaerobic curable component. Advantageously, the composition of the present invention is substantially solid and may be used as a threadlocker.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an anaerobic curable composition that can be used in many applications, including as a thread locking agent. The composition is substantially solid and may be provided in any suitable solid form, including tape form, filament form, or as a coating that is applied to a substrate, including, for example, a filament or thread made from another material, such as nylon or polyester thread. The present invention also relates to a method of making a threaded fastener and a method of assembling a threaded fastener. The composition is easily handled and can be applied to a threaded member. The composition is heat resistant at a temperature of at least 150°C. [Background technology]

[0002] Thread locking compositions are used to lock and / or seal threaded fasteners, such as nuts and bolts, in their mated state. Such thread locking compositions significantly increase the torque required to break or turn engaged threaded fasteners. Conventional thread locking compositions often include co-reactive adhesive systems, in which two or more components are mixed together prior to application of the resulting composition to the thread-engaging surface of a fastener, where the components in the thread locking composition react and cure. Examples of such co-reactive systems include epoxy resin adhesive compositions.

[0003] Liquid adhesive compositions have long been used for sealing and threadlocking applications and have become a standard part of assembly production as well as maintenance of machines, tools, etc. Among the liquid adhesive compositions commonly used in these applications are anaerobic compositions. These compositions provide excellent threadlocking and sealing properties upon curing. Anaerobic curable compositions that are applied to threaded fasteners as threadlocking compositions remain stable (uncured) and liquid until placed between mated threaded fasteners and cured in the absence of oxygen.

[0004] Anaerobic curing compositions are generally known (see, for example, R. D. Rich, "Anaerobic Adhesives," in Handbook of Adhesive Technology, vol. 29, pp. 467-79, edited by A. Pizzi and K. L. Mittal, Marcel Dekker Company, New York (1994), and references cited therein). Their uses are numerous, and new applications continue to be developed.

[0005] Anaerobic adhesive systems are stable in the presence of oxygen but will polymerize in the absence of oxygen. Polymerization is initiated by the presence of free radicals, often generated from peroxy compounds. Anaerobic adhesive compositions are well known for their ability to remain in a liquid, unpolymerized state in the presence of oxygen and cure to a solid state when oxygen is excluded.

[0006] Anaerobic adhesive systems often contain resin monomers terminated with polymerizable acrylic esters, such as methacrylates, ethyl acrylates, and chloroacrylate esters derived according to known urethane chemistry, e.g., polyethylene glycol dimethacrylates and urethane acrylates (e.g., U.S. Pat. No. 3,425,988 (Gorman)). Other components typically present in anaerobically curable adhesive compositions include initiators, such as organic hydroperoxides, e.g., cumene hydroperoxide, tertiary butyl hydroperoxide, accelerators to increase the cure rate of the composition, and stabilizers, such as quinones or hydroquinones, that are included to prevent premature polymerization of the adhesive due to decomposition of the peroxy compounds.

[0007] Desirable cure-inducing compositions for inducing and accelerating anaerobic cure may include one or more of saccharin, toluidines such as N,N-diethyl-p-toluidine ("DE-pT") and N,N-dimethyl-O-toluidine ("DE-oT"), and acetylphenylhydrazines ("APH") with maleic acid. See, e.g., U.S. Patent Nos. 3,218,305 (Creble), 4,180,640 (Melody), 4,287,330 (Rich), and 4,321,349 (Rich).

[0008] Saccharin and APH are used as standard accelerator components in anaerobic adhesive cure systems. In fact, many of the Loctite® brand anaerobic adhesive products currently available from Henkel use either saccharin alone or both.

[0009] Anaerobic curable adhesive compositions also commonly include a chelating agent, such as ethylenediaminetetraacetic acid (EDTA), which is used to sequester metal ions.

[0010] Compositions suitable for use in pre-applied threadlocking applications are typically applied in a dry to the touch form, but with the capability for later anaerobic curing.

[0011] In some cases, a dry feel shape may be achieved using a curing mechanism, for example, a first curing mechanism may form a dry feel shape to hold the composition in place on the article, and then a second curing mechanism may be activated to achieve thread lock.

[0012] For example, EP 0077659 (Thompson) describes a pre-applied polymerizable fluid for sealing and fastening engineered parts. The composition has two curing mechanisms and two curing reactions occur. The first mechanism is curing by UV light. An opacifying agent is dispersed in the fluid, rendering the fluid substantially opaque to radiation. After application of the liquid to the part, exposure to UV light forms a coating, forming a dry, tack-free surface layer. The liquid below the skin is unaffected by the radiation and generally remains in a liquid state. When the part is screwed into another part, the surface layer breaks down and a second polymerization (e.g., free radical polymerization) is initiated, and a second curing reaction occurs when an anaerobic environment is established as the threaded parts engage. The second polymerization mechanism functions to lock the threads together. In Thompson, only the skin is formed in the first polymerization, while the remainder of the composition remains liquid below the skin. Thus, there is a risk that the skin breaks down during handling of the coated engineered part, resulting in leakage of the fluid composition.

[0013] Similarly, EP 0548369 (USAMI) describes a pre-applied adhesive composition for application to the threaded contact surfaces of threaded members such as screws. The composition includes a photocurable binder having dispersed therein a secondary curable composition including microencapsulated reactive monomer / activator / initiator.

[0014] WO 2004 / 024841 A2 (Haller) describes a curable composition for application to threaded articles. The composition comprises a dispersion of components of a first cure mechanism comprising (a) a (meth)acrylate-functional monomer component, (b) a (meth)acrylate-functional oligomer component, and (c) a photoinitiator component; and (ii) components of a second cure mechanism comprising (e) an amine component, and (f) an encapsulated epoxy resin component; and (iii) a thickener component. The photoinitiator component is suitable for achieving a first cure throughout the depth of the composition applied to the threaded article upon irradiation of the composition, such that a binder matrix is ​​formed by the components of the second cure mechanism dispersed in the matrix.

[0015] U.S. Patent No. 9,181,457 (Atarwala) describes a dry feel composition that contains a polymer matrix and an anaerobic curable component present within the polymer matrix. In a particularly desirable form, the composition is moisture curable. The composition is non-flowable at elevated temperatures and exhibits improved solvent resistance upon curing. The composition is useful as a threadlocking composition and can be formulated as a coating on a carrier substrate such as a tape, string, or sheet.

[0016] British Patent No. 2,543,756 (Redwith) describes a threadlock composition comprising an anaerobic curable component and a curing component for curing said anaerobic curable component. Here, the composition is in a flowable particulate form and has a melting point in the range of 30 to 100°C. The anaerobic curable component may comprise an anaerobic curable monomer and a resin component. The composition may be provided in at least a two-part form. The anaerobic curable component is preferably provided in the form of a powder. Preferably, the resin component is selected from a methacrylated polyurethane resin, a novolac resin, or a higher methacrylated polyester resin. The anaerobic curable monomer preferably comprises at least one acrylate or methacrylate group. The composition is preferably solvent-free. Also disclosed is a method of thread-locking two threaded articles comprising applying the composition to the threads of at least one article so that it welds to the threads, and then, optionally after cooling, threading the two articles together to initiate anaerobic curing of the thread-locking composition and chemically bond the two articles. Also disclosed is an article to which the composition has been applied.

[0017] U.S. Patent Application Publication No. 4,039,705 (Duek) relates to anaerobically curable pressure sensitive adhesive stocks such as sheets and tapes that include a pressure sensitive adhesive layer that includes at least one anaerobic resin system that is capable of transferring completely to one substrate and adhering to another substrate and curing upon activation by a peroxy initiator and exclusion of oxygen. The anaerobic pressure sensitive adhesive is contained between two different release surfaces, and upon curing of the anaerobic curable pressure sensitive adhesive, the adhesive can transfer to the substrate to securely hold the substrate in place.

[0018] Although conventional anaerobic threadlockers have been and continue to be popular in the marketplace, there are drawbacks in certain commercial applications that have been observed with the use of conventional liquid anaerobic threadlockers and known non-flowing thixotropic anaerobic threadlockers. For example, in many cases, such compositions do not cure completely through large gaps. Also, due to the nature of anaerobic curing, the portions of the adhesive that remain exposed to air after application to the part are less likely to cure (unless a secondary cure mechanism is triggered). Thus, external bond lines that remain exposed to air on nut / bolt assemblies often remain liquid unless additional additives or curing measures are taken to ensure cure. As a result, the liquid composition of the external bond line has a tendency to migrate. In the case of conventional non-flowing compositions, the non-flowing depends on the thixotropic and / or rheological properties of the composition, but these compositions will flow if the temperature to which they are exposed is high enough. Additionally, the solvent resistance of the cured product (those that have portions that remain uncured as described above) may be poor, indicating questionable integrity when environmental interactions occur. This can cause contamination issues and hazardous conditions in the surroundings.

[0019] Despite the state of the art, it would be desirable to provide alternative thread-locking systems that include threaded members that include a dry feel thread-locking composition, methods of forming such threaded members, and methods of assembling such threaded members. [Prior art documents] [Patent documents]

[0020] [Patent Document 1] U.S. Patent No. 3,425,988 [Patent Document 2] U.S. Patent No. 3,218,305 [Patent Document 3] U.S. Patent No. 4,180,640 [Patent Document 4] U.S. Patent No. 4,287,330 [Patent Document 5] U.S. Patent No. 4,321,349 [Patent Document 5] European Patent No. 0077659 [Patent Document 5] European Patent No. 0548369 [Patent Document 5] International Patent Publication 2004 / 024841A2 [Patent Document 5] U.S. Patent No. 9,181,457 [Patent Document 5] British Patent No. 2,543,756 [Patent Document 5] U.S. Patent Application Publication No. 4,039,705 [Non-patent literature]

[0021] [Non-Patent Document 1] R. D. Rich, "Anaerobic Adhesives," in Handbook of Adhesion Technology, vol. 29, pp. 467-79, edited by A. Pizzi and K. L. Mittal, Marcel Dekker Company, New York (1994). Summary of the Invention [Means for solving the problem]

[0022] In one aspect, the present invention provides a method for producing a method for treating a cancer cell comprising: Liquid anaerobic hardening component; Solid anaerobic hardening components; A solid thermoplastic polyether polyurethane resin; and a curing component for curing the anaerobic curable component; The present invention provides an anaerobic curable composition comprising:

[0023] Advantageously, the compositions of the present invention are substantially solid and can be used to provide any suitable solid form.The compositions of the present invention can be used for any suitable application.For example, they can be provided on threaded articles in solid form, in thread form, or in tape form.The compositions of the present invention can be provided on a carrier or can be self-supporting.

[0024] The solid thermoplastic polyether polyurethane resin has a molecular weight Mw in the range of about 180,000 g / mol to about 260,000 g / mol, suitably in the range of about 200,000 g / mol to about 240,000 g / mol, such as about 215,000 g / mol to 230,000 g / mol, such as 220,000 g / mol to 225,000 g / mol, such as about 223,000 g / mol, as measured in accordance with ASTM D5296-05 (Standard Test Method for Molecular Weight Average and Molecular Weight Distribution of Polystyrene by High Performance Size Exclusion Chromatography).

[0025] The solid thermoplastic polyether polyurethane resin may have a melting point in the range of 160°C to 200°C, such as 165°C to 190°C, for example 170°C to 180°C.

[0026] The liquid anaerobic curable component may be present in an amount of about 20% to about 50% by weight based on the total weight of the curable composition, suitably about 30% to about 40% by weight based on the total weight of the curable composition, for example about 36% by weight based on the total weight of the curable composition. If the liquid anaerobic curable component is present in an amount less than about 20% by weight based on the total weight of the composition, the composition may be too hard / non-flowable when applied / coated to a substrate and may not move well, for example, may not move into spaces between interlocking threads that are threaded together, and may have poor thread locking performance or poor adhesive performance. If the liquid anaerobic curable component is present in an amount greater than about 50% by weight based on the total weight of the composition, the integrity on the part may be adversely affected, the composition may be too flowable / too soft, for example, the coating formed by the composition may break easily when in contact with other surfaces, such as the surfaces of handling equipment or other substrates, including other substrates to which the coating may be applied. When the liquid anaerobic curable component is present in an amount of about 20% to about 50% by weight based on the total weight of the curable composition, compositions are provided that have an acceptable balance between threadlock and / or adhesive performance, as well as compositions that form coatings with sufficient integrity and cure to provide good bond strength, the integrity necessary for application of the composition to the parts being bonded, and the bond strength required for the end use of the bond.

[0027] The solid anaerobic curable component may be present in an amount of about 8% to about 30% by weight based on the total weight of the composition, suitably about 10% to about 25% by weight based on the total weight of the composition, for example, 15% to about 22% by weight based on the total weight of the curable composition. Compositions containing less than about 8% by weight of the solid anaerobic curable component tend to lack cohesion and may not be suitable for partial application. For example, coatings formed by such compositions may easily rupture when in contact with other surfaces, such as surfaces of handling equipment or other substrates, including other substrates to which the coating is applied. Compositions containing more than about 30% by weight of the solid anaerobic curable component tend to form coatings that are too brittle to apply to the parts to be bonded. When the solid anaerobic curable component is present in an amount of about 8% to about 30% by weight based on the total weight of the composition, compositions having an acceptable balance between thread lock and / or adhesive performance (when cured) (when applied as a coating) and compositions that can be applied as a coating with sufficient integrity and strength are provided.

[0028] The solid thermoplastic polyether polyurethane resin may be present in an amount of about 10% to about 30% by weight based on the total weight of the curable composition, suitably about 18% to about 25% by weight based on the total weight of the curable composition, for example about 20% by weight based on the total weight of the curable composition. Compositions containing less than about 10% by weight of the solid thermoplastic polyether polyurethane component tend to have insufficient elastomeric properties to allow proper application of the composition to the parts to be bonded. Compositions containing more than about 30% by weight of the solid thermoplastic polyether polyurethane component tend to exhibit insufficient thread lock / adhesive properties. When the solid thermoplastic polyether polyurethane resin is present in an amount of about 10% to about 30% by weight based on the total weight of the curable composition, a composition having an acceptable balance between thread lock and / or adhesive performance, as well as a composition capable of forming a coating with sufficient elastomeric properties to allow application of the composition to the parts to be bonded, is provided.

[0029] The curing component for curing the anaerobic curable component may be present in an amount of from about 0.1 to about 10 wt % based on the total weight of the curable composition, for example, from about 1 to about 5 wt % based on the total weight of the curable composition.

[0030] Suitably, the liquid anaerobic curable component comprises a liquid (meth)acrylate monomer component.

[0031] The liquid (meth)acrylate monomer component has the formula: 2 C=CGCO 2 R 8 wherein G is hydrogen, halogen, or an alkyl group having 1 to about 4 carbon atoms; 8 is selected from alkyl, cycloalkyl, alkenyl, cycloalkenyl, alkaryl, aralkyl, or aryl groups having 1 to about 16 carbon atoms, any of which may be optionally substituted or interrupted with silane, silicon, oxygen, halogen, carbonyl, hydroxyl, ester, carboxylic acid, urea, urethane, carbonate, amine, amide, sulfur, sulfonate, sulfone, and the like.

[0032] Suitably, the solid anaerobic curable component comprises one or more solid (meth)acrylate monomer components. For example, the anaerobically curable solid can be the reaction product of phenyl isocyanate and hydroxyethyl methacrylate (HEMA):

[0033] [ka]

[0034] This is a 2-methacryloxyethyl urethane with a melting point of about 70-75°C.

[0035] The solid anaerobic curable component can be the reaction product of two molar equivalents of HEMA with one molar equivalent of a diisocyanate such as isophorone diisocyanate (IPDI), 4,4'-methylenebis(cyclohexylisocyanate) (hMDI), 1,5-cyclohexyl diisocyanate (CHDI), etc. For example:

[0036] [ka]

[0037] This is HEMA-IPDI-HEMA with a melting point of about 72-74°C.

[0038] [ka]

[0039] This is HEMA-hMDI-HEMA, which has a melting point of about 75-85°C.

[0040] [ka]

[0041] This is HEMA-CHDI-HEMA with a melting point of about 75-85°C.

[0042] The solid anaerobic curable component may be a polyurethane methacrylate resin having a molecular weight >2000 g·mol and with a semi-crystalline polyester polyol backbone. An example of such a resin is described in International Patent Publication WO 2017 / 68196 A1 and is the reaction product of a polyol known as Dynacol 7380 with toluene diisocyanate, followed by end-capping with HEMA. The melting points of these resins are in the range of 50-80°C.

[0043] Novolac vinyl ester resins, which are the reaction products of novolac epoxy resins and methacrylic acid, are also useful as solid anaerobic curable components. Examples of these resins and their preparation are shown in U.S. Patent No. 9,957,344. For example:

[0044] [ka]

[0045] In the formula, n is an integer of 2 to 10, and the melting point of the compound is about 70 to 75°C.

[0046] Suitably, the curing component comprises one or more selected from the group consisting of 1-acetyl-2-phenylhydrazine, N,N-dimethyl para toluidine, N,N-diethyl para toluidine, N,N-diethanol para toluidine, N,N-dimethyl orthotoluidine, N,N-dimethyl meta toluidine, indoline, 2-methyl indoline, isoindoline, indole, 1,2,3,4-tetrahydroquinoline, 3-methyl-1,2,3,4-tetrahydroquinoline, 2-methyl-1,2,3,4-tetrahydroquinoline, 1,2,3,4-tetrahydroquinoline-4-carboxylic acid, and 1,2,3,4-tetrahydro-benzo(H)quinolin-3-ol.

[0047] The anaerobic curable composition of the present invention may include a cure accelerator, which includes the following:

[0048] [ka]

[0049] In the formula, X is CH 2 ,O,S,NR 4 , C.R. 5 R 6 or C=O; R is one or more of hydrogen, alkyl, alkenyl, alkyne, hydroxyalkyl, hydroxyalkenyl, or hydroxyalkyne; R 1 ~R 6are each selected from hydrogen, halogen, amino, carboxyl, nitro, alkyl, alkenyl, alkynyl, hydroxyalkyl, hydroxyalkenyl, hydroxyalkynyl, or alkaryl; R 7 is hydrogen or CHR 8 R 9 and R 8 and R 9 are each selected from hydrogen, halogen, amino, carboxyl, nitro, alkyl, alkenyl, alkynyl, hydroxyalkyl, hydroxyalkenyl, hydroxyalkynyl, or alkaryl; and n is 0 or 1.

[0050] Optionally, the above cure accelerators are used in combination with at least one co-accelerator selected from the group consisting of amines, amine oxides, sulfonamides, metal sources, acids, and mixtures thereof.

[0051] For example, the co-promoter may be selected from the group consisting of triazine, ethanolamine, diethanolamine, triethanolamine, N,N-dimethylaniline, benzenesulfanimide, cyclohexylamine, triethylamine, butylamine, saccharin, N,N-diethyl-p-toluidine, N,N-dimethyl-O-toluidine, acetylphenylhydrazine, maleic acid, and mixtures thereof.

[0052] The cure accelerator may be:

[0053] [ka]

[0054] wherein R is one or more of hydrogen, alkyl, alkenyl, alkynyl, hydroxyalkyl, hydroxyalkenyl, or hydroxyalkynyl; R 1 and R 2are each independently selected from halogen, amino, carboxyl, nitro, alkyl, alkenyl, alkynyl, hydroxyalkyl, hydroxyalkenyl, hydroxyalkynyl, or alkaryl.

[0055] For example, the cure accelerator may be selected from one or more of the following:

[0056] [ka]

[0057] The cure accelerator may be:

[0058] [ka]

[0059] The compositions of the present invention may further comprise an initiator of free radical polymerization, such as a peroxide.

[0060] The initiator for the free radical polymerization is one or more selected from the group consisting of cumene hydroperoxide ("CHP"), para-menthane hydroperoxide, t-butyl hydroperoxide ("TBH"), t-butyl perbenzoate, benzoyl peroxide, dibenzoyl peroxide, 1,3-bis(t-butylperoxyisopropyl)benzene, diacetyl peroxide, butyl 4,4-bis(t-butylperoxy)valerate, p-chlorobenzoyl peroxide, t-butylcumyl peroxide, t-butyl perbenzoate, di-t-butyl peroxide, dicumyl peroxide, 2,5-dimethyl-2,5-di-t-butylperoxyhexane, 2,5-dimethyl-2,5-di-t-butyl-peroxyhex-3-yne, 4-methyl-2,2-di-t-butylperoxypentane, t-amyl hydroperoxide, 1,2,3,4-tetramethylbutyl hydroperoxide, and combinations thereof. Initiators of free radical polymerization may include encapsulated peroxides.

[0061] The composition of the present invention may further comprise a cure accelerator in addition to or instead of the above. For example, the cure accelerator may comprise one or more metallocenes, such as ferrocene, suitably n-butylferrocene. Advantageously, the presence of the cure accelerator accelerates the cure of the composition of the present invention on "non-active" or "passive" substrates, such as plastic substrates.

[0062] The composition of the present invention may further comprise at least one solvent.The use of a solvent may be beneficial, for example, for the purpose of blending or distribution.Suitably, the at least one solvent may be selected from the group comprising tetrahydrofuran, dichloromethane, chloroform, or combinations thereof.

[0063] However, when weight percent is used, it is based on the total weight of the composition without the solvent.

[0064] Suitably, the composition of the present invention may be provided in any suitable solid form, including tape form, filament form, or as a coating applied to a substrate, including filaments or threads made from another material, such as nylon or polyester threads. A tape or filament of the solid composition may be less than 100 microns (μm) thick. The tape or filament may be applied by winding, i.e., in a manner similar to current PTFE tape or thread seal cords used to seal pipe joints. It will be understood that the solid form may be in any desired pattern or arrangement, including sticks, tapes, filaments, gaskets, or patches. The composition in a solid form, such as a tape or filament form, may have sufficient integrity to be handled without breaking. The composition in a solid form, such as a tape or filament form, may be applied to a substrate, such as a metal bolt, at room temperature. The composition in a solid form, such as a tape or filament form, may have heat resistance at a temperature of at least 150° C., such as 180° C., meaning that the composition is robust enough to maintain performance at temperatures in typical industrial environments. Even at high temperatures, the composition in a solid form, such as a tape or filament form, is non-tacky and dry to the touch, so no carrier such as a release liner is required. The composition in a tape or filament form can be wound on itself and does not adhere to itself, since it is non-tacky and dry to the touch. Alternatively, the tape or filament form may comprise the anaerobic curable composition described herein and one or more release liners. For example, if the temperature at which the composition is stored is above 40° C., a release liner may be useful, since at temperatures above 40° C., a non-tacky composition may become tacky and stick to itself. As mentioned above, the composition of the present invention may be in any suitable solid form, including a tape, filament, or may be a (solid, dry to the touch) coating applied to a substrate, including filaments or threads made of other materials, such as nylon or polyester threads.

[0065] Another aspect of the present invention provides a cured composition formed by curing the inventive curable composition claimed herein. Suitably, the curable composition may be cured by exposure to an anaerobic environment. The curable composition may be cured by exposure to an anaerobic environment for a time ranging from about 1 minute to about 30 minutes, such as from about 1 minute to about 20 minutes. Optionally, the curable composition may be cured within a temperature range of about 40°C to about 100°C. For example, the curable composition may be cured by exposure to an anaerobic environment for a time ranging from about 1 minute to about 30 minutes within a temperature range of about 40°C to about 100°C.

[0066] Once cured, the compositions of the present invention desirably exhibit breaking torque values ​​of greater than 10 Nm against black oxidized mild steel or zinc phosphate substrates when evaluated on M10 nuts and bolts according to ISO 10964. Furthermore, the cured compositions of the present invention desirably exhibit loosening torque values ​​of greater than 10 Nm at temperatures up to 180°C, for example at 50°C, 80°C, 120°C, 150°C, or 180°C, when evaluated on zinc phosphate M10 nuts and bolts according to ISO 10964.

[0067] In another aspect, the present invention provides a threaded member including at least one threaded surface, the at least one threaded surface comprising an anaerobic curable composition as described herein. For example, the anaerobic curable composition may be in tape-like or filament form. Alternatively, it may be in the form of a composition applied / coated to threads made of different materials. A tape, thread, or fiber may be applied to the threaded surface, for example, by wrapping the tape, thread, or fiber at least partially around the threaded surface. For example, the anaerobic curable composition may be coated onto a thread or fiber made of a different material to form a coated thread or fiber. The coated thread or fiber may be applied to the threaded surface, for example, by wrapping the coated thread or fiber at least partially around the threaded surface.

[0068] In yet another aspect, the present invention is a method of manufacturing a threaded member comprising a thread locking composition, comprising the steps of providing at least one threaded member comprising at least one threaded surface, and applying to said at least one threaded surface an anaerobic curable composition as described herein. Suitably, the anaerobic curable composition is applied to the at least one threaded surface in tape form, filament form, or as a coating applied to a substrate such as a thread form or fiber formed from a different material, for example the tape, filament, or coated substrate is at least partially wrapped around at least one threaded surface of the threaded member. Suitably, the anaerobic curable composition in tape form, filament, or coated substrate is non-tacky and dry feeling, so that no carrier such as a release liner is required.

[0069] In yet another aspect, the present invention provides a method of assembling threaded members, comprising the steps of: providing a first threaded member including at least one threaded surface; applying an anaerobic curable composition described herein to the at least one threaded surface; providing a second threaded member matingly engageable with the first threaded member; matingly engaging the first threaded member and the second threaded member, thereby exposing the anaerobic curable composition to an anaerobic environment for a period of time sufficient for the anaerobic curable composition to cure between the first threaded member and the second threaded member.

[0070] Also provided is a method for producing a threadlocking tape, thread, or fiber, comprising the steps of: (i) mixing at least one solid thermoplastic polyether polyurethane resin and a solvent; the solid thermoplastic polyether polyurethane resin optionally has a molecular weight Mw in the range of about 180,000 g / mol to about 260,000 g / mol, suitably in the range of about 200,000 g / mol to about 240,000 g / mol, such as about 215,000 g / mol to 230,000 g / mol, for example 220,000 g / mol to 225,000 g / mol, for example about 223,000 g / mol, wherein the molecular weight Mw is measured according to ASTM D5296-05, and optionally has a melting point of 160° C. to 200° C., such as 165° C. to 190° C., for example 170° C. to 180° C.; suitably the solvent may be selected from tetrahydrofuran, dichloromethane, chloroform, or a combination thereof; (ii) mixing a liquid anaerobically hardenable component, a solid anaerobically hardenable component, and a hardening component for hardening the anaerobically hardenable component, and optionally adding an additive to the mixture; (iii) forming the mixture into a desired shape, for example, by casting or extruding the mixture and / or applying it to a carrier such as a threaded article or a release liner; Removing the solvent and / or evaporating the solvent to form a tape, thread, or fiber comprising the anaerobic curable composition described herein and optionally a carrier. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0071] As generally described above, the present invention provides an anaerobically curable composition comprising a liquid anaerobic curable component; a solid anaerobic curable component; a solid thermoplastic polyether polyurethane resin; and a curing component for curing the anaerobic curable component.

[0072] (Definitions and standard test methods) The term "liquid" refers to the liquid state within a temperature range of about 5° C. to 30° C., suitably at room temperature and atmospheric pressure.

[0073] The term "solid" refers to the solid state within the temperature range of about 5° C. to 40° C., suitably at room temperature and atmospheric pressure. The solid state is defined as a state of matter in which the material is not fluid, retains its boundaries without support, and the atoms or molecules occupy fixed positions relative to one another and are not free to move.

[0074] In the context of the present invention, tack-free means that the composition feels dry but does not fall off during handling or use.For example, an article coated with the composition of the present invention feels dry.An article coated with the composition of the present invention is considered to feel dry if 20 such articles are placed individually on dry tissue paper for 4 hours and there is no change in the appearance of the tissue.

[0075] Molecular weights disclosed herein are measured according to ISO 13885-1:2008 "Binders for paints and varnishes, gel permeation chromatography (GPC), part 1: tetrahydrofuran (THF) as eluent."

[0076] The melting and resolidification temperature ranges were measured according to ISO 1137-1:2016 "Plastics, Differential Scanning Calorimetry (DSC), Part 1 General Principles."

[0077] (Liquid anaerobic hardening component) Suitably, the liquid anaerobic curable component comprises a liquid (meth)acrylate monomer component.

[0078] The liquid (meth)acrylate components are: β-carboxyethyl acrylate, isobornyl acrylate, n-octyl acrylate, n-decyl acrylate, cyclohexyl acrylate, tetrahydrofurfuryl acrylate, 2-ethylhexyl acrylate, ethoxyethoxyethyl acrylate, ethoxylated phenyl monoacrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxybutyl acrylate, isooctyl acrylate, n-butyl acrylate, neopentyl glycol diacrylate, ethylene glycol diacrylate, diethylene glycol diacrylate, dipropylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, 1,6-hexanediol diacrylate, tripropylene glycol diacrylate, glycerol triacrylate, trimethylolpropane diacrylate, trimethylolpropane triacrylate. acrylate, pentaerythritol tetraacrylate, phenoxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, cyclohexyl methacrylate, glycerol mono-methacrylate, glycerol 1,3-dimethacrylate, trimethylcyclohexyl methacrylate, methyl triglycol methacrylate, isobornyl methacrylate, trimethylolpropane trimethacrylate, neopentyl glycol dimethacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, 1,6-hexanediol dimethacrylate, hydroxybutyl methacrylate, tetrahydrofurfuryl methacrylate, cyclohexyl methacrylate, phenoxyethyl methacrylate, glycerol methacrylate, glycidyl methacrylate, methyl methacrylate and methacrylic acid, and mixtures thereof.

[0079] Preferred liquid (meth)acrylate monomers include 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, tetrahydrofurfuryl methacrylate, isobornyl methacrylate, phenoxyethyl methacrylate, and methacrylic acid.

[0080] The one or more suitable (meth)acrylates may be selected from among, but are not limited to, di- or trifunctional (meth)acrylates such as polyethylene glycol di(meth)acrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate ("TRIEGMA"), tetraethylene glycol dimethacrylate, dipropylene glycol dimethacrylate, di-(pentamethylene glycol) dimethacrylate, tetraethylene diglycol diacrylate, diglycerol tetramethacrylate, tetramethylene dimethacrylate, ethylene dimethacrylate, neopentyl glycol diacrylate, trimethylolpropane triacrylate, polyethylene glycol di(meth)acrylate, and multifunctional (meth)acrylates such as bisphenol-A mono- and di(meth)acrylates, e.g., ethoxylated bisphenol-A (meth)acrylate ("EBIPMA"), and bisphenol-F mono- and di(meth)acrylates, e.g., ethoxylated bisphenol-F (meth)acrylate.

[0081] For example, the redox curable component may include bisphenol A dimethacrylate:

[0082] [ka]

[0083] Suitably, the redox curable composition may contain ethoxylated bisphenol A di(meth)acrylate.

[0084] Still other (meth)acrylates that may be suitable for use herein are the silicone (meth)acrylate moieties ("SiMA"), such as those taught and claimed by U.S. Pat. No. 5,605,999 (Chu), the disclosure of which is expressly incorporated herein.

[0085] Other suitable materials may be selected from polyacrylates represented by the formula:

[0086] [ka]

[0087] In the formula, R 4 is a group selected from hydrogen, halogen, or alkyl having 1 to about 4 carbon atoms, q is an integer at least equal to 1, preferably 1 to about 4, and X is an organic group containing at least 2 carbon atoms and having a total binding capacity of q plus 1. With respect to the upper limit of the number of carbon atoms in X, essentially any usable monomer can exist. However, as a practical matter, a typical upper limit is about 50 carbon atoms, for example, preferably about 30, and preferably about 20.

[0088] For example, X can be an organic group of the formula:

[0089] [ka]

[0090] In the formula, Y 1 and Y 2 Each of Z is an organic group, such as a hydrocarbon group, containing at least 2 carbon atoms, desirably from 2 to about 10 carbon atoms, and Z is an organic group, preferably a hydrocarbon group, containing at least 1 carbon atom, preferably from 2 to about 10 carbon atoms. Other materials may be selected from reaction products of di- or tri-alkylolamines (e.g., ethanolamine or propanolamine) with acrylic acid, as disclosed in French Patent No. 1,581,361.

[0091] Suitable oligomers having (meth)acrylate functionality may also be used. Examples of such (meth)acrylate functionalized oligomers include those having the general formula:

[0092] [ka]

[0093] In the formula, R 5 represents a group selected from hydrogen, alkyl having 1 to about 4 carbon atoms, and hydroxyalkyl having 1 to about 4 carbon atoms; or

[0094] [ka]

[0095] In the formula, R 4 is a group selected from hydrogen, halogen, or alkyl having 1 to about 4 carbon atoms; R 6 is a group selected from hydrogen, hydroxyl, or

[0096] [ka]

[0097] m is an integer at least equal to 1, for example, 1 to about 15 or more, desirably 1 to about 8; n is an integer at least equal to 1, for example, 1 to about 40 or more, desirably about 2 to about 10; and p is 0 or 1.

[0098] Representative examples of acrylic ester oligomers corresponding to the above general formula include di-, tri-, and tetraethylene glycol dimethacrylate; di(pentamethylene glycol) dimethacrylate; tetraethylene glycol diacrylate; tetraethylene glycol di(chloroacrylate); diglycerol diacrylate; diglycerol tetramethacrylate; butylene glycol dimethacrylate; neopentyl glycol diacrylate; and trimethylolpropane triacrylate.

[0099] Diacrylates and other polyacrylates, particularly the polyacrylates described in the previous paragraph, are preferred, although monofunctional acrylates (esters containing one acrylate group) may also be used.

[0100] Suitable compounds may be selected from among cyclohexyl methacrylate, tetrahydrofurfuryl methacrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate, t-butylaminoethyl methacrylate, cyanoethyl acrylate, and chloroethyl methacrylate.

[0101] Another useful class of materials are the reaction products of (meth)acrylate-functionalized hydroxyl- or amino-containing materials with polyisocyanates in appropriate proportions to convert all isocyanate groups to urethane or ureido groups, respectively.

[0102] The (meth)acrylate urethane or urea ester thus formed may contain hydroxy or amino functional groups in the non-acrylate portion. (Meth)acrylic acid esters suitable for use may be selected from among those of the following formulae:

[0103] [ka] wherein X is selected from --O-- and the following:

[0104] [ka]

[0105] In the formula, R 9 is selected from hydrogen or lower alkyl having 1 to 7 carbon atoms; R 7 is selected from hydrogen, halogen (such as chlorine), or alkyl (such as methyl and ethyl); R 8 is a divalent organic group selected from alkylene, phenylene, and naphthylene having 1 to 8 carbon atoms.

[0106] These groups, when appropriately reacted with a polyisocyanate, produce monomers of the general formula:

[0107] [ka]

[0108] where n is an integer from 2 to about 6; B is a polyvalent organic radical selected from alkyl, alkenyl, cycloalkyl, cycloalkenyl, aryl, alkaryl, alkaryl, and substituted and unsubstituted heterocyclic radicals, and combinations thereof; R 7 , R 8 and X has the above meaning.

[0109] Depending on the nature of B, these (meth)acrylic acid esters having urea or urethane bonds may have a molecular weight that falls into the oligomeric class (for example, from about 1,000 g / mol to about 5,000 g / mol) or polymeric class (greater than about 5,000 g / mol).

[0110] Other unsaturated reactive monomers and oligomers can be used, such as styrenes, maleimides, vinyl ethers, allyls, allyl ethers, and those described in U.S. Patent No. 6,844,080 (Kniefsee et al.). Vinyl resins such as those described in U.S. Patent No. 6,433,091 (Shea) can also be used. Methacrylate or acrylate monomers containing these unsaturated reactive groups can also be used.

[0111] Of course, combinations of these (meth)acrylates with other monomers may also be used.

[0112] (Solid anaerobic hardening component) The anaerobic curable composition of the present invention comprises a solid anaerobic curable component. The solid anaerobic curable component may be a solid (meth)acrylate resin. Suitably, the solid (meth)acrylate resin is selected from the list of suitable (meth)acrylate components given above.

[0113] (Solid thermoplastic polyether polyurethane resin) The anaerobic curable composition of the present invention comprises a solid thermoplastic polyether polyurethane resin. The solid thermoplastic polyether polyurethane resin may have a molecular weight Mw in the range of about 180,000 g / mol to about 260,000 g / mol, suitably in the range of about 200,000 g / mol to about 240,000 g / mol, for example about 215,000 g / mol, for example about 215,000 g / mol to 230,000 g / mol, for example 220,000 g / mol to 225,000 g / mol, for example about 223,000 g / mol, the molecular weight Mw being measured according to ASTM D5296-05. The solid thermoplastic polyether polyurethane resin may have a melting point of 160°C to 200°C, for example 165°C to 190°C, for example 170°C to 180°C. Suitable solid thermoplastic polyether polyurethane resins include Pearlbond® 960, available from Lubrizol, Carrer del Gran Vial, 17, 08160 Montmeló, Barcelona, ​​Spain. Pearlbond® 960 is a solid thermoplastic polyether polyurethane resin with a Mw of 222,906 as measured in accordance with D5296-05 (Standard Test Method for Molecular Weight Average and Molecular Weight Distribution of Polystyrene by High Performance Size Exclusion Chromatography) and a melting point in the range of 170°C to 180°C. EXAMPLES

[0114] The anaerobic curable compositions shown in Table 1 were formulated into a tape form.

[0115] [Table 1]

[0116] *The resin used was a polyurethane methacrylate resin which is the reaction product of a diisocyanate endcapped with a methacrylate (HPMA). **The red dye is a non-ionic polymeric colorant. In these examples, Reactint® Red (no CAS number assigned), available from Milliken, was used. "Amt" = amount

[0117] The compositions in Table 1 were prepared as follows. The solid thermoplastic polyether polyurethane was dissolved in ethyl acetate at a temperature of about 70°C before being transferred to a Speedmixer DAC150.147. The remaining ingredients were then added and mixing was continued until each ingredient was dissolved. For compositions containing microencapsulated peroxides or methacrylates, the encapsulated ingredients did not dissolve and mixing was continued until the microencapsulated ingredients formed a dispersion in the solution. Each solution was then cast onto a siliconized polyester release liner (HiFi SR4-122, 75 micron thickness) using an Elcometer 4340 automatic film coater with the coating plate temperature maintained at 30°C. After coating, the ethyl acetate was allowed to evaporate from the heated coating plate. A dry-feeling film was obtained.

[0118] As used herein in relation to the present invention, the words "comprises" and "comprising" are used to specify the presence of stated features, integers, steps or components, but do not exclude the presence or addition of one or more of other features, integers, steps, components, or groups thereof.

[0119] It is appreciated that certain features of the invention, which are, for clarity, described in the context of separate embodiments, may also be provided in combination in a single embodiment. Conversely, various features of the invention, which are, for brevity, described in the context of a single embodiment, may also be provided separately or in any suitable subcombination.

[0120] The threadlocking performance of each film formed from the compositions of the present invention identified in Table 1 was evaluated on M10 nuts and bolts according to ISO 10964. The compositions of the present invention were applied to an M10 bolt to form a threaded assembly with an M10 nut capable of matingly engaging with the M10 bolt. The threaded assembly was held at room temperature (20° C.-25° C.) for 24 hours before measuring the break strength and prevail strength of the cured compositions. The results for each composition on various substrates are shown in Table 2.

[0121] [Table 2]

[0122] The compositions of the present invention were applied to M10 zinc phosphate bolts with metal spacers to form threaded assemblies with M10 nuts that could be matingly engaged with the M10 bolts with an applied force of 5 Nm. The threaded assemblies were held at room temperature (20°C to 25°C) for 168 hours, after which the break strength and prevail strength of the compositions cured at specific temperatures were measured. The results for each composition at various temperatures are shown in Table 3.

[0123] [Table 3]

Claims

1. Liquid anaerobic curing component; Solid anaerobic hardening component; A solid thermoplastic polyether polyurethane resin; and a curing component for curing the anaerobic curable component; An anaerobic curable composition comprising: An anaerobic curable composition, wherein said solid thermoplastic polyether polyurethane resin has a molecular weight Mw in the range of about 180,000 g / mol to about 260,000 g / mol, said molecular weight Mw being determined according to ASTM D5296-05.

2. 2. The composition of claim 1, wherein the solid thermoplastic polyether polyurethane resin has a molecular weight Mw in the range of about 200,000 g / mol to about 240,000 g / mol, such as about 215,000 g / mol to 230,000 g / mol, such as 220,000 g / mol to 225,000 g / mol, such as about 223,000 g / mol, wherein the molecular weight Mw is determined according to ASTM D5296-05.

3. 3. A composition according to claim 1 or 2, wherein the solid thermoplastic polyether polyurethane resin has a melting point of from 160°C to 200°C, such as from 165°C to 190°C, for example from 170°C to 180°C.

4. 3. The composition of claim 1 or 2, wherein the liquid anaerobic curable component is present in an amount of about 20% to about 50% by weight based on the total weight of the composition, suitably about 30% to about 40% by weight, for example about 36% by weight based on the total weight of the curable composition.

5. 3. The composition of claim 1 or 2, wherein the solid anaerobic curable component is present in an amount of about 8% to about 30% by weight based on the total weight of the composition, suitably about 10% to about 25% by weight, for example 15% to about 22% by weight based on the total weight of the curable composition.

6. 3. The composition of claim 1 or 2, wherein the solid thermoplastic polyether polyurethane resin is present in an amount of about 10% to about 30% by weight based on the total weight of the composition, suitably about 18% to about 25% by weight, for example about 20% by weight based on the total weight of the curable composition.

7. 3. The composition of claim 1 or 2, wherein the curing component for curing the anaerobic curable component is present in an amount of about 0.1 to about 10 wt %, for example about 1 to about 5 wt %, based on the total weight of the curable composition.

8. The composition of claim 1 or 2, wherein the liquid anaerobically curable component comprises a liquid (meth)acrylate monomer component.

9. The liquid (meth)acrylate monomer component has the formula: 2 C=CGCO 2 R 8 The composition of claim 8, wherein the one or more are selected from the group consisting of: where G is hydrogen, halogen, or an alkyl group having 1 to about 4 carbon atoms; R 8 is selected from alkyl, cycloalkyl, alkenyl, cycloalkenyl, alkaryl, aralkyl, or aryl groups having 1 to about 16 carbon atoms, any of which may be optionally substituted or interrupted with silane, silicon, oxygen, halogen, carbonyl, hydroxyl, ester, carboxylic acid, urea, urethane, carbonate, amine, amide, sulfur, sulfonate, sulfone, and the like.

10. 3. The composition of claim 1 or 2, wherein the solid anaerobic curable component comprises one or more solid (meth)acrylate monomer components.

11. 3. The composition of claim 1 or 2, wherein the curing component comprises one or more selected from the group consisting of 1-acetyl-2-phenylhydrazine, N,N-dimethyl paratoluidine, N,N-diethyl paratoluidine, N,N-diethanol paratoluidine, N,N-dimethyl orthotoluidine, N,N-dimethyl metatoluidine, indoline, 2-methylindoline, isoindoline, indole, 1,2,3,4-tetrahydroquinoline, 3-methyl-1,2,3,4-tetrahydroquinoline, 2-methyl-1,2,3,4-tetrahydroquinoline, 1,2,3,4-tetrahydroquinoline-4-carboxylic acid, and 1,2,3,4-tetrahydro-benzo(H)quinolin-3-ol.

12. 3. The composition of claim 1 or 2, further comprising an initiator of free radical polymerization, such as a peroxide.

13. The initiator for the free radical polymerization may be selected from the group consisting of cumene hydroperoxide ("CHP"), para-menthane hydroperoxide, t-butyl hydroperoxide ("TBH"), t-butyl perbenzoate, benzoyl peroxide, dibenzoyl peroxide, 1,3-bis(t-butylperoxyisopropyl)benzene, diacetyl peroxide, butyl 4,4-bis(t-butylperoxy)valerate, p-chlorobenzoyl peroxide, t-butylcumyl peroxide, t 13. The composition of claim 12, wherein the tert-butyl peroxy group is one or more selected from the group consisting of 2,5-dimethyl-2,5-di-t-butylperbenzoate, di-t-butyl peroxide, dicumyl peroxide, 2,5-dimethyl-2,5-di-t-butylperoxyhexane, 2,5-dimethyl-2,5-di-t-butyl-peroxyhex-3-yne, 4-methyl-2,2-di-t-butylperoxypentane, t-amyl hydroperoxide, 1,2,3,4-tetramethylbutyl hydroperoxide, and combinations thereof.

14. The composition of claim 12 , wherein the initiator of free radical polymerization comprises an encapsulated peroxide.

15. The composition of claim 1 or 2, further comprising a cure accelerator.

16. the cure accelerator is one or more metallocenes, such as ferrocene, suitably n-butylferrocene; and / or 【Chemistry 1】 (Wherein, X is CH 2 , O, S, N.R. 4 , C.R. 5 R 6 or C=O; R is one or more of hydrogen, alkyl, alkenyl, alkyne, hydroxyalkyl, hydroxyalkenyl, or hydroxyalkyne; R 1 ~R 6 are each selected from hydrogen, halogen, amino, carboxyl, nitro, alkyl, alkenyl, alkynyl, hydroxyalkyl, hydroxyalkenyl, hydroxyalkynyl, or alkaryl; R 7 is hydrogen or CHR 8 R 9 and R 8 and R 9 are each selected from hydrogen, halogen, amino, carboxyl, nitro, alkyl, alkenyl, alkynyl, hydroxyalkyl, hydroxyalkenyl, hydroxyalkynyl, or alkaryl; and n is 0 or 1. A curing accelerator included in The composition of claim 15 comprising:

17. 3. The composition of claim 1 or 2 provided in the form of a tape, filament, or coated substrate.

18. 3. The composition of claim 1 or 2 provided as a coating on a yarn or fiber.

19. A tape comprising the anaerobic curable composition of claim 1 or 2 and one or more release liners.

20. 3. A threaded member comprising at least one threaded surface, the at least one threaded surface comprising the anaerobic curable composition of claim 1 or 2, optionally in the form of a tape, filament, or coated substrate, and optionally wherein the anaerobic curable composition in the form of a tape, filament, or coated substrate is applied to the threaded surface, for example, by wrapping the tape at least partially around the threaded surface.

21. a. providing at least one threaded member including at least one threaded surface; b. applying to the at least one threaded surface an anaerobic curable composition according to claim 1 or 2; A method of making a threaded member comprising the threadlocking composition, comprising:

22. 22. The method of claim 21, wherein the anaerobic curable composition is in the form of a tape, filament, or coated substrate, and optionally the anaerobic curable composition in the form of a tape, filament, or coated substrate is at least partially wrapped around the at least one threaded flank of the threaded member.

23. (a) providing a first threaded member including at least one threaded surface; (b) applying the anaerobic curable composition of claim 1 or 2 to the at least one threaded surface; (c) providing a second threaded member matingly engagable with the first threaded member; matingly engaging the first and second threaded members and exposing the anaerobically curable composition to an anaerobic environment for a time sufficient for the anaerobically curable composition to cure between the first and second threaded members; A method for assembling a screw member, comprising:

24. 24. The method of claim 23, wherein the anaerobic curable composition is in tape form, filament form, or coated substrate form, and optionally the anaerobic curable composition in tape form, filament form, or coated substrate form is at least partially wrapped around the at least one threaded surface.

25. (i) combining at least one solid thermoplastic polyether polyurethane resin with a solvent; said solid thermoplastic polyether polyurethane resin optionally has a molecular weight Mw in the range of about 180,000 g / mol to about 260,000 g / mol, suitably in the range of about 200,000 g / mol to about 240,000 g / mol, for example about 215,000 g / mol to 230,000 g / mol, such as 220,000 g / mol to 225,000 g / mol, for example about 223,000 g / mol, wherein the molecular weight Mw is measured according to ASTM D5296-05; The solid thermoplastic polyether polyurethane resin optionally has a melting point of from 160° C. to 200° C., e.g., from 165° C. to 190° C., e.g., from 170° C. to 180° C.; Suitably, the solvent is selected from tetrahydrofuran, dichloromethane, chloroform, or a combination thereof. (ii) mixing a liquid anaerobically hardenable component, a solid anaerobically hardenable component, and a hardening component for hardening the anaerobically hardenable component, and optionally adding an additive to the mixture; (iii) forming the mixture into a desired shape, for example by casting and / or spreading the mixture onto a carrier, such as a threaded article or a release line; removing the solvent and / or evaporating the solvent to form a tape, thread, or fiber comprising the anaerobic curable composition described herein and optionally a carrier; 2. A method for producing a threadlocking tape, thread, or fiber, comprising: